A comprehensive review on mixotrophic denitrification processes for biological nitrogen removal. (February 2023) - Zhang, Jintao; Fan, Chunzhen; Zhao, Min; Wang, Zhiquan; Jiang, Shunfeng; Jin, Zhan; Bei, Ke; Zheng, Xiangyong; Wu, Suqing; Lin, Ping; Miu, Huanyi
Abstract: Biological denitrification is the most widely used method for nitrogen removal in water treatment. Compared with heterotrophic and autotrophic denitrification, mixotrophic denitrification is later studied and used. Because mixotrophic denitrification can overcome some shortcomings of heterotrophic and autotrophic denitrification, such as a high carbon source demand for heterotrophic denitrification and a long start-up time for autotrophic denitrification. It has attracted extensive attention of researchers and is increasingly used in biological nitrogen removal processes. However, so far, a comprehensive review is lacking. This paper aims to review the current research status of mixotrophic denitrification and provide guidance for future research in this field. It is shown that mixotrophic denitrification processes can be divided into three main kinds based on different kinds of electron donors, mainly including sulfur-, hydrogen-, and iron-based reducing substances. Among them, sulfur-based mixotrophic denitrification is the most widely studied. The most concerned influencing factors of mixotrophic denitrification processes are hydraulic retention times (HRT) and ratio of chemical oxygen demand (COD) to total inorganic nitrogen (C/N). The dominant functional bacteria of sulfur-based mixotrophic denitrification system are Thiobacillus, Azoarcus, Pseudomonas, and Thauera. At present, mixotrophic denitrification processes are mainly applied for nitrogen removal in drinking water, groundwater, and wastewater treatment. Finally, challenges and future research directions are discussed. Graphical abstract: Image 1 Highlights: Mixotrophic denitrification processes for biological nitrogen removal were reviewed. Sulfur-, hydrogen-, and iron-based reducing substances are the main electron donors. The most concerned influencing factors are HRT and C/N ratio. The main application areas are drinking water, groundwater, and wastewater treatment. Mixotrophic denitrification is efficient for biological nitrogen removal in water.